Efficacy and safety of lifileucel, a one-time autologous tumor-infiltrating lymphocyte (TIL) cell therapy, in patients with advanced melanoma after progression on immune checkpoint inhibitors and targeted therapies: pooled analysis of consecutive cohorts of the C-144-01 study - Chesney, Jason; Lewis, Karl D.; Kluger, Harriet; Hamid, Omid; Whitman, Eric; Thomas, Sajeve; Wermke, Martin; Cusnir, Mike; Domingo-Musibay, Evidio; Phan, Giao Q.; Kirkwood, John M.; Hassel, Jessica C.; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Patients with advanced melanoma have limited treatment options after progression on immune checkpoint inhibitors (ICI). Lifileucel, a one-time autologous tumor-infiltrating lymphocyte (TIL) cell therapy, demonstrated an investigator-assessed objective response rate (ORR) of 36% in 66 patients who progressed after ICI and targeted therapy. Herein, we report independent review committee (IRC)-assessed outcomes of 153 patients treated with lifileucel in a large multicenter Phase 2 cell therapy trial in melanoma. - Methods Eligible patients had advanced melanoma that progressed after ICI and targeted therapy, where appropriate. Melanoma lesions were resected (resected tumor diameter ≥1.5 cm) and shipped to a central good manufacturing practice facility for 22-day lifileucel manufacturing. Patients received a non-myeloablative lymphodepletion regimen, a single lifileucel infusion, and up to six doses of high-dose interleukin-2. The primary endpoint was IRC-assessed ORR (Response Evaluation Criteria in Solid Tumors V.1.1). - Results The Full Analysis Set consisted of 153 patients treated with lifileucel, including longer-term follow-up on the 66 patients previously reported. Patients had received a median of 3.0 lines of prior therapy (81.7% received both anti-programmed cell death protein 1 and anti-cytotoxic lymphocyte-associated protein 4) and had high disease burden at baseline (median target lesion sum of diameters (SOD): 97.8 mm; lactate dehydrogenase (LDH) >upper limit of normal: 54.2%). ORR was 31.4% (95% CI: 24.1% to 39.4%), with 8 complete responses and 40 partial responses. Median duration of response was not reached at a median study follow-up of 27.6 months, with 41.7% of the responses maintained for ≥18 months. Median overall survival and progression-free survival were 13.9 and 4.1 months, respectively. Multivariable analyses adjusted for Eastern Cooperative Oncology Group performance status demonstrated that elevated LDH and target lesion SOD >median were independently correlated with ORR (p=0.008); patients with normal LDH and SOD <median had greater likelihood of response than those with either (OR=2.08) or both (OR=4.42) risk factors. The most common grade 3/4 treatment-emergent adverse events (≥30%) were thrombocytopenia (76.9%), anemia (50.0%), and febrile neutropenia (41.7%). - Conclusions Investigational lifileucel demonstrated clinically meaningful activity in heavily pretreated patients with advanced melanoma and high tumor burden. Durable responses and a favorable safety profile support the potential benefit of one-time lifileucel TIL cell therapy in patients with limited treatment options in ICI-refractory disease.